IoT-Based Early Warning Detection System for LPG Leakage Using Raspberry Pi - Azman, Muhammad Iqbal; Wan Kairuddin, Wan Nur Hafsha (Evolution in Electrical and Electronic Engineering, 2022)
Liquefied Petroleum Gas (LPG) is one of the household things in daily life. LPG, on the other hand, is extremely combustible. Many accidents have occurred as a result of LPG leaking. A detection and monitoring system is quite widespread in the industrial field. However, this approach is still uncommon in the domestic market. Since LPG is commonly used in homes, an early warning detection system for LPG leakage is critical. This project seeks to solve this problem by creating a device that uses a sensor and an exhaust fan connected to a Raspberry Pi 4. This system will detect the LPG leakage through the sensor while activating the alarm and exhaust fan. This system simultaneously alerts the user using a real-time message to the authorized users through Telegram Messenger on their smartphones. Users will be able to utilise this device to prevent accidents caused by gas leaks, allowing accidents to be prevented. This LPG leakage detection system has been developed successfully that is suitable to be used in a small confined area such as the kitchen. This system ensures safety and prevents explosions due to gas leakage.